2019
DOI: 10.3390/antiox8090376
|View full text |Cite
|
Sign up to set email alerts
|

Linking What We Eat to Our Mood: A Review of Diet, Dietary Antioxidants, and Depression

Abstract: Studies have shown that diet and nutrition play significant roles in the prevention of depression and its clinical treatment. The present review aims to provide a clear understanding of the associations between diet patterns, specific foods, nutrients such as antioxidants, and depression. As a result, balanced dietary patterns such as the Mediterranean diet and certain foods such as fish, fresh vegetables, and fruits have been associated with a lower risk of depression or depressive symptoms, while high-fat We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 150 publications
(175 reference statements)
2
71
1
7
Order By: Relevance
“…This result is consistent with recently published systematic literature studies showing a consistent result. A balanced diet with high intake of vegetables, fruits, and fish was associated with reduced risk of depression, whilst a diet with added sugar, soda, and junk food was associated with increased risk of depression [42][43][44]. The results of the present study and other recently published results strengthen Berk et al [3] results and thus their presented guidelines.…”
Section: Discussionsupporting
confidence: 85%
“…This result is consistent with recently published systematic literature studies showing a consistent result. A balanced diet with high intake of vegetables, fruits, and fish was associated with reduced risk of depression, whilst a diet with added sugar, soda, and junk food was associated with increased risk of depression [42][43][44]. The results of the present study and other recently published results strengthen Berk et al [3] results and thus their presented guidelines.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the fact that our research also found no direct relationship between depression and sweet drink consumption. This contrasts with previous research which identified an association between depression and sweetened beverages (e.g., Knüppel et al, 2017 ; Huang et al, 2019 ). Some of these findings on this relationship were a bit more ambiguous on closer examination, though.…”
Section: Discussioncontrasting
confidence: 99%
“…Notwithstanding the limited evidence, many authors of narrative reviews come to firm conclusions about the effects of a diet on depression (e.g. : “Studies have shown that diet and nutrition play a significant role in the prevention and clinical treatment of depression” (page 10) [ 20 ]). On the contrary, authors of systematic reviews seem to come to less firm conclusions (e.g., "The results of this meta-analysis suggest that healthy pattern may decrease the risk of depression, whereas western-style may increase the risk of depression.…”
Section: Introductionmentioning
confidence: 99%